The social foundations of racial inequalities in arrest over the life course and in changing times - Sampson, Robert J. (Criminology, 2024)
Although racial disparities in criminal justice contact are long-standing and the subject of continuing public debate, few studies have linked early-life social conditions to racial disparities in arrest over the life course and in changing times. In this article, we advance and test a theoretical model of racial inequality in long-term arrest histories on a representative sample of nearly 1,000 individuals from multiple birth cohorts in the Project on Human Development in Chicago Neighborhoods. Large Black-White disparities in arrests from ages 10 to 40 arise from racial inequalities in exposure to cumulative childhood advantages and disadvantages rather than from race-specific effects. Smaller but meaningful Hispanic-White gaps follow a similar pattern, and the same explanations of racial disparities hold across different offense types and across birth cohorts who came of age at different times during 1995 to 2021. These findings indicate that inequalities in early-life structural factors, which themselves are historically shaped, trigger processes of cumulative advantage and disadvantage that produce racial disparities in arrests over the life course and that persist across different points in contemporary history.